2019
DOI: 10.1016/j.tibtech.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Sensors in Cancer

Abstract: In 2006, the group of Dr C.M. Lieber pioneered the field of nanowire sensors by fabricating devices for the ultra-sensitive label-free detection of biological macromolecules. Since then, nanowire sensors have demonstrated their ability to detect cancer-associated analytes in peripheral blood, tumor tissue, and the exhaled breath of cancer patients. These innovative developments have marked a new era with unprecedented detection performance, capable of addressing crucial needs such as cancer diagnosis and monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 112 publications
(155 reference statements)
0
62
0
Order By: Relevance
“…[295][296][297][298][299] By considering metal-oxide NWs, in 2017 Zhang et al [178] exploited the resistive switching properties of ZnO NWs for the realization of gas sensors with high selectivity and improved recovery speed. Recently, it was shown that the memristive properties of suspended Si NWs realized by a top down approach can be strongly modulated by the presence of biomolecules, making possible the realization of highly sensitive biosensors.…”
Section: Memsensorsmentioning
confidence: 99%
“…[295][296][297][298][299] By considering metal-oxide NWs, in 2017 Zhang et al [178] exploited the resistive switching properties of ZnO NWs for the realization of gas sensors with high selectivity and improved recovery speed. Recently, it was shown that the memristive properties of suspended Si NWs realized by a top down approach can be strongly modulated by the presence of biomolecules, making possible the realization of highly sensitive biosensors.…”
Section: Memsensorsmentioning
confidence: 99%
“…Such devices bring promises in order to have cost effective point of care (POC) and highly multiplexed sensors for personalised precision medicines [25] .…”
Section: Introductionmentioning
confidence: 99%
“…As 1D nanoscale electron transport channels with a large surface‐to‐volume ratio, semiconductor nanowire FET transducers are highly sensitive in the detection of bioelectrical signals, such as biomolecular charges or cell membrane potentials. Several sensor configurations are commonly applied, such as FETs, memristors, and capture array nanowires, among which FETs have received extensive attention due to the analyte flexibility (miRNA, ctDNA, and drugs) . In an FET sensor, the perturbation of the electric potential at the nanowire surface associated with binding events of charged biomolecules (the sign and quantities of their charges depend on the isoelectric point of the biomolecules and the solution pH) leads to a change in the charge‐carrier density and conductance of nanowire FET devices in real time .…”
Section: Chemical/biological Sensorsmentioning
confidence: 99%
“…Several sensor configurations are commonly applied, such as FETs, memristors, and capture array nanowires, among which FETs have received extensive attention due to the analyte flexibility (miRNA, ctDNA, and drugs). 178 In an FET sensor, the perturbation of the electric potential at the nanowire surface associated with binding events of charged biomolecules (the sign and quantities of their charges depend on the isoelectric point of the biomolecules and the solution pH) leads to a change in the charge-carrier density and conductance of nanowire FET devices in real time. 179 Toward advantageous surfacebiological environment activity, the design of semiconductor nanowires via compositional and structural engineering is important.…”
Section: Nanowire Biological Sensorsmentioning
confidence: 99%